Efisiensi Penggunaan Faktor Produksi Pada Usahatani Cabai Besar di Desa Titigalar - Ferdinandus Kewu; Cening Kardi; Ni Putu Sukanteri (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
Big chili is a superior horticultural commodity that has high economic value and is widely cultivated by farmers in Indonesia. Large chili farming in Indonesia still faces various obstacles, both technical and economic constraints. This study aims to determine the production factors that affect the production of Big Chili in Titigalar Village and to determine the efficiency of the use of production factors in the Big Chili farming in Titigalar Village. Which was carried out from June to July 2020. The results showed that the production factors that influenced the production of Big Chili farming in Titigalar Village were: Chili seeds had a significant effect on production elasticity of 0.326, Urea fertilizer had no significant effect with production elasticity of 0.114, Fertilizer NPK has a significant effect with a production elasticity of 0.419, Organic Fertilizer has a significant effect with a production elasticity of 0.153, Liquid Pesticides have a significant effect with a production elasticity of 0.140 and Labor has a significant effect with a production elasticity of 0.068. The efficiency level of the use of production factors in Big Chili farming in the KelurahanTigalar, namely: Large Chili Seeds, Urea Fertilizers, NPK Fertilizers, Organic Fertilizers, Liquid Pesticides, and Labor are not efficient.